1997
DOI: 10.1007/s002530051085
|View full text |Cite
|
Sign up to set email alerts
|

Competition of plasmid-bearing Pseudomonas putida strains catabolizing naphthalene via various pathways in chemostat culture

Abstract: Plasmid-carrying Pseudomonas putida strains degrade naphthalene through different biochemical pathways. The influence of various combinations of host bacteria and plasmids on growth characteristics and competitiveness of P. putida strains was studied in chemostat culture at a low dilution rate (D = 0.05 h-1) with naphthalene as the sole source of carbon and energy. Under naphthalene limitation, the plasmid-bearing strains degrading naphthalene that use catechol 1,2-dioxygenase for catechol oxidation (ortho pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…16 In some cases, salicylate can be accumulated in the culture medium during the microbial degradation of naphthalene in batch culture. 20 As salicylate was not found in the soil extracts, the most probable scenario seems to be accumulation of salicylate utilization 21 are in favor of this suggestion. The authors observed a lag period between the degradation of the substrate and the active bacterial growth in studies of the possible use of salicylate for a selective increase of the metabolic activity and growth stimulation of P putida G7 in soil microcosms.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…16 In some cases, salicylate can be accumulated in the culture medium during the microbial degradation of naphthalene in batch culture. 20 As salicylate was not found in the soil extracts, the most probable scenario seems to be accumulation of salicylate utilization 21 are in favor of this suggestion. The authors observed a lag period between the degradation of the substrate and the active bacterial growth in studies of the possible use of salicylate for a selective increase of the metabolic activity and growth stimulation of P putida G7 in soil microcosms.…”
Section: Discussionmentioning
confidence: 75%
“…Powdered naphthalene was not distributed uniformly in the soil sample, so a solution of naphthalene in a low-boiling point solvent (pentane) was employed. A 100 cm 3 aliquote of 0.2% naphthalene solution in pentane was added into a flask with 100 g of sterile dry soil, and then the flask was shaken (200 rpm) for 2 h at room temperature (20 • C) to distribute the naphthalene evenly and to evaporate the solvent. As the soil was mixed with naphthalene, nearly half of the naphthalene was evaporated with the pentane.…”
Section: Soil Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlates with the fact of catechol-2,3-dioxygenase activity in pOV17-harboring strains being higher than that in pBS216-bearing strains. It is known the strains able to degrade catechol via the meta-pathway demonstrate high specific growth rates [35][36][37]. P. chlororaphis PCL1391(pBS216) had the maximum growth rate and colonized plant rhizosphere well (nearly 1.5 Â 10 8 CFU g À1 rhizosphere).…”
Section: Discussionmentioning
confidence: 99%
“…The methodological framework described has been implemented in the development of the environmental biosensor for the detection of polycyclic aromatic hydrocarbons (PAHs) in estuarine areas. These hydrocarbons are usually found in sediments buried and persist there till their degradation, resuspension, bioaccumulation and removal by river sludge deposition (Filonov et al [1]). Nowadays, much is known about the rate and chemical pathways of PAHs in water or sediment interfaces.…”
Section: Methodological Frameworkmentioning
confidence: 99%